2019
DOI: 10.1111/cas.13902
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe suppresses development of liver tumors by inhibiting angiogenesis in mice fed a high‐fat diet

Abstract: Nonalcoholic steatohepatitis (NASH) is a common cause of liver cirrhosis and hepatocellular carcinoma (HCC). However, effective therapeutic strategies for preventing and treating NASH‐mediated liver cirrhosis and HCC are lacking. Cholesterol is closely associated with vascular endothelial growth factor (VEGF), a key factor that promotes HCC. Recent reports have demonstrated that statins could prevent HCC development. In contrast, we have little information on ezetimibe, an inhibitor of cholesterol absorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…No study had investigated the biological functions for the eight lncRNAs identified in HCC; however, they could affect the genesis as well as the progression of HCC by the Wnt signaling pathway[20-24], angiogenesis[25,26], p53 pathway[27,28], and PI3 kinase pathways[29-31], as suggested by the pathway enrichment results. More importantly, this research could provide new evidence that lncRNAs, whose biological functions had not been reported before, might potentially serve as the potent markers to predict the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…No study had investigated the biological functions for the eight lncRNAs identified in HCC; however, they could affect the genesis as well as the progression of HCC by the Wnt signaling pathway[20-24], angiogenesis[25,26], p53 pathway[27,28], and PI3 kinase pathways[29-31], as suggested by the pathway enrichment results. More importantly, this research could provide new evidence that lncRNAs, whose biological functions had not been reported before, might potentially serve as the potent markers to predict the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, NASH-driven hepatocarcinogenesis is mechanistically involved in the process of necrosis formation in the tumor microenvironment, and the latter has also been related to enhanced infiltration with immune-competent cells [5][6][7][8][9]. Furthermore, experimental studies reported on novel angiogenic pathways playing a key role in de novo or NASH-driven hepatocarcinogenesis, implicating the complex immunologic mechanisms involved in cancer progression [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Non-alcoholic steatohepatitis (NASH) is a common cause of cirrhosis and hepatocellular carcinoma (HCC). Studies have shown that a high-fat diet promotes serum cholesterol levels in mice liver, subsequently increases vascular endothelial-derived growth factor (VEGF) levels, and ultimately leads to high proliferation of liver tumor cells [49]. STAB2 acts as a scavenger receptor and is implicated in cell apoptosis [50].…”
Section: Discussionmentioning
confidence: 99%